Paparan Drama Tiongkok terhadap Pandangan Realitas Budaya Tiongkok pada Penonton di Indonesia - Jennifer Grace; Riris Loisa (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
This study is motivated by the growing penetration of Chinese dramas in Indonesia, which are increasingly competing with the dominance of Korean dramas, particularly among viewers aged 18–35 who are active consumers of digital media. This phenomenon indicates that foreign entertainment plays a role in shaping cross-cultural perceptions and has become part of the dynamics of cultural globalization. The study aims to measure the influence of exposure to foreign entertainment products on viewers’ perceptions of the reality of the producing culture, using Cultivation Theory as the main framework to explain how intensive and repetitive exposure can affect audiences’ understanding, attitudes, and behavioral tendencies. Variables such as frequency, duration, attention, and viewer involvement are derived from the concepts of media exposure and foreign entertainment, while the process of cultural perception formation is explained through the concept of stereotypes within the warmth–competence framework. This research employs a quantitative approach through an online survey of 100 respondents who meet the criteria of Chinese drama viewers. The findings affirm that foreign entertainment media plays a significant role as an agent of cultural transmission and contributes to shaping how audiences interpret cultural realities within the context of contemporary globalization. Penelitian ini dilatarbelakangi oleh meningkatnya penetrasi drama Tiongkok di Indonesia yang kini bersaing dengan dominasi drama Korea, terutama pada kelompok penonton berusia 18–35 tahun yang menjadi konsumen aktif media digital. Fenomena ini menunjukkan bahwa hiburan asing berperan dalam membentuk persepsi budaya lintas negara dan menjadi bagian dari dinamika globalisasi budaya. Studi ini bertujuan mengukur pengaruh terpaan produk hiburan asing terhadap pandangan tentang realitas budaya produsen dengan menggunakan Teori Kultivasi sebagai landasan utama untuk menjelaskan bagaimana terpaan yang intensif dan berulang mampu memengaruhi pemahaman, sikap, serta kecenderungan perilaku penonton. Variabel frekuensi, durasi, atensi, dan keterlibatan penonton dijelaskan melalui konsep terpaan media dan hiburan asing, sedangkan proses pembentukan persepsi budaya dijelaskan menggunakan konsep stereotip dalam kerangka warmth dan competence. Metode penelitian yang digunakan adalah pendekatan kuantitatif melalui survei daring kepada 100 responden yang memenuhi kriteria penonton drama Tiongkok. Temuan ini menegaskan bahwa media hiburan asing memiliki peran signifikan sebagai agen transmisi budaya dan turut membentuk cara audiens memaknai realitas budaya dalam konteks globalisasi kontemporer.